The role of demographics to actual purchase decision in online shopping - Safitri, Dina; Nabila, Nuzul Inas; Sari, Aida; Ramelan, Mudji Rahmat (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2024)
Recovery Version (See for detail) This study looks at the factors that influence Indonesian customers' online buying behavior, with a focus on demographics like gender, age, occupation, income, and trust. Using a novel technique that treats demographics as independent variables, the study investigates their differential effects on actual purchases made using bank cards and cash-on-delivery (COD). According to hierarchical regression research, gender has a substantial influence on both bank card and COD purchases, with females having a lower propensity for online transactions. Age was not found to be a significant predictor of bank card purchases, but occupation had a positive relationship with COD transactions, showing that those in higher-status occupations are more inclined to use COD. Income did not significantly predict either manner of purchasing, and trust had only a minor impact on bank card transactions. The study emphasizes the importance of demographic considerations in understanding online shopping behavior, with implications for policymakers, industry practitioners, and academics looking to support long-term growth in Indonesia's e-commerce ecosystem. Article Information: Received 1/30/2023 / Revised 6/22/2024 / Accepted 6/23/2024 / Online First 6/30/2024